IMPLEMENTASI ASESMEN FORMATIF BERBASIS DIGITAL DALAM PEMBELAJARAN TEKS HIKAYAT SISWA KELAS X SMK - Purwanti; Suhelvi; Dina; Aceng Hasani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The digital transformation of education requires assessment practices that function not only as evaluation tools but also as instruments to enhance student engagement and understanding throughout the learning process. One alternative approach is the implementation of digital formative assessment through the Socrative application. This study aims to examine the role of digital formative assessment using Socrative in improving students’ engagement and comprehension in learning hikayat texts. The research employed a qualitative descriptive approach involving 30 tenth-grade students of SMK Madinatul Hadid, Cilegon City. Data were collected through open-ended questionnaires and classroom observations during the learning process. Data analysis was conducted using content analysis techniques, including coding, tabulation, and thematic interpretation, supported by data triangulation to enhance the validity of the findings. The results indicate that the implementation of digital formative assessment positively influenced students’ engagement, motivation, and active participation in learning activities. Furthermore, the use of Socrative helped students understand the structure and content of hikayat texts more effectively through immediate feedback that encouraged reflection and improvement of comprehension. Although several technical challenges related to internet connectivity and device availability were identified, these issues were not experienced by most students. Therefore, digital formative assessment using Socrative can be considered an effective alternative for supporting student-centered learning and aligning with the principles of the Merdeka Curriculum. ABSTRAK Transformasi pembelajaran pada era digital menuntut penggunaan asesmen yang tidak hanya berfungsi sebagai alat evaluasi, tetapi juga mampu meningkatkan keterlibatan dan pemahaman siswa selama proses belajar. Salah satu alternatif yang dapat diterapkan adalah asesmen formatif berbasis digital melalui aplikasi Socrative. Penelitian ini bertujuan untuk mengkaji peran asesmen formatif berbasis digital menggunakan Socrative dalam meningkatkan keterlibatan dan pemahaman siswa pada pembelajaran teks hikayat. Penelitian menggunakan pendekatan deskriptif kualitatif dengan subjek 30 siswa kelas X SMK Madinatul Hadid Kota Cilegon. Data dikumpulkan melalui angket terbuka dan observasi selama proses pembelajaran. Analisis data dilakukan menggunakan teknik analisis isi yang meliputi tahap koding, tabulasi, dan interpretasi tematik, serta diperkuat dengan triangulasi data untuk meningkatkan validitas temuan. Hasil penelitian menunjukkan bahwa implementasi asesmen formatif berbasis digital memberikan dampak positif terhadap keterlibatan, motivasi, dan partisipasi aktif siswa dalam pembelajaran. Penggunaan Socrative juga membantu siswa memahami struktur dan isi teks hikayat secara lebih efektif melalui penyediaan umpan balik langsung yang mendorong refleksi dan perbaikan pemahaman. Meskipun ditemukan beberapa kendala teknis terkait jaringan internet dan ketersediaan perangkat, hambatan tersebut tidak dialami oleh sebagian besar siswa. Dengan demikian, asesmen formatif berbasis digital menggunakan Socrative terbukti menjadi alternatif yang efektif dalam mendukung pembelajaran yang berpusat pada siswa dan sejalan dengan prinsip implementasi Kurikulum Merdeka.